Development Of Pedagogic Competence Of Madrasah Aliyah Teachers Through Independent Curriculum Workshop - Apri Pil Bahrul Ulum; Ichwanul taufiq Nasution; Muhammad Hendra Yusren; Pratama Avriyansyah; Salamun Salamun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of teachers' pedagogic competence is a crucial factor in the successful implementation of the Independent Curriculum in Madrasah Aliyah. This article aims to analyze the urgency of developing teachers' pedagogic competence, the principles and concepts of the Independent Curriculum, as well as the role of workshops as a teacher professional development strategy. This research uses a qualitative literature study method, by reviewing literature related to pedagogic competence, the Independent Curriculum, and teacher training. The results of the study show that Madrasah Aliyah teachers face significant challenges in differentiated learning, authentic assessment, and the integration of character and religious values. The Independent Curriculum provides flexible, project-based, and student-centered learning principles that require teachers to have high pedagogic competence. The Independent Curriculum Workshop has proven to be effective as a professional development strategy, as it provides hands-on practical experience, builds a collaborative culture, and improves teachers' skills in designing and implementing innovative learning. The relationship between workshops and improving pedagogic competence can be seen from the teacher's ability to apply authentic assessments, differentiated learning, and the integration of character and religious values. Thus, the development of pedagogic competencies through workshops is a strategic step to improve the quality of education at Madrasah Aliyah, producing teachers who are competent, creative, critical, and able to prepare students with Islamic characters.